The spillover effects of economic policy uncertainty in Latin America on the Spanish economy - Corinna Ghirelli; Javier J. Pérez; Alberto Urtasun (Latin American Journal of Central Banking (LAJCB), 2021)
We construct economic policy uncertainty (EPU) indexes for a number of Latin American (LA) economies (Argentina, Brazil, Chile, Colombia, Mexico, Peru, Venezuela) and the region as a whole, based on reports in the Spanish press. Our measures are comparable across countries. We study the macroeconomic effects of LA EPU shocks on the analyzed American economies and the Spanish economy. To study the international spillover effects on the Spanish economy, we carry out two exercises by means of vector auto-regression models. First, we estimate responses to unexpected shocks in LA EPU of the quotations of Spanish companies which are highly exposed to Latin America. Second, we study the impact of LA EPU shocks on Spanish macroeconomic aggregates. Unexpected shocks in LA EPU significantly dampen commercial relationships between Spain and LA countries. Spanish firms decrease their exports and foreign direct investments in LA countries that experience negative shocks in EPU.
Keywords: D8; C43; E2; E3; 330; Economic policy uncertainty; Latin America's economies; Uncertainty shocks